PERANAN IBU RUMAH TANGGA DALAM MENINGKATKAN STATUS SOSIAL KELUARGA DI KELURAHAN BAHU KECAMATAN MALALAYANG KOTA MANADO - Tenda, Hutri Paulina Utami; Tumengkol, Selvie M.; Kawung, Evelin J. R. (HOLISTIK, Journal Of Social and Culture, 2020)
Status is the position of a person in a group and its relationship with other members in that group, or the position of a group compared to other groups that are more numerous. Because one's position in a group is related to what he does, or is expected to do, then status is closely related to role. In a family the role of a housewife is very important in order to improve the social status of the family. The role is usually performed by the head of the household, but with all the limitations cause housewives to intervene to help the husbands. This is a common phenomenon no exception for housewives who are in the Kelurahan Bahu District of Malalayang, Manado City.From the results of the study, the researchers concluded that from the four aspects seen about social status, only aspects in various unions were considered not too important, the informants prioritized the primary need to improve their family's social status.Keywords: housewife, social status, family